Convective Flow of a Ferrofluid Between Rotating Stretchable Disks in An Anisotropic Porous Medium - K. Gowthami, Hari Prasad. P, B. Mallikarjuna (International Journal of Advanced Science and Technology, 2020)
In this paper, Ferro-fluid flow between1 two stretchable 1rotating disks in an orthotropic porous medium is presented. Governing equations1 for the problem are formulated and non-dimensionalized using appropriate transformations. Results are computed using shooting method. Results are explained using figures and table values of various values of physical parameters effective magnetization parameter, volume concentration of magnetic parameter and rotation parameter